1975
DOI: 10.1021/jf60202a017
|View full text |Cite
|
Sign up to set email alerts
|

Cheddar cheese flavor. Review of current progress

Abstract: Recent reexaminations of methods of isolating cheese volatiles are noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…As a result, considerable interest has focused on the enzymol-ogy and molecular biology of the lactococcal proteinase system and the impact that these enzymes have on desirable flavors and bitterness (Thomas and Mills, 1981;Kok, 1990;OIson, 1990). Free amino acids are thought to be precursors for background chee se flavor compounds, but the mechanism is largely undefined (McGugan, 1975;Adda et al, 1982;Law, 1987;OIson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, considerable interest has focused on the enzymol-ogy and molecular biology of the lactococcal proteinase system and the impact that these enzymes have on desirable flavors and bitterness (Thomas and Mills, 1981;Kok, 1990;OIson, 1990). Free amino acids are thought to be precursors for background chee se flavor compounds, but the mechanism is largely undefined (McGugan, 1975;Adda et al, 1982;Law, 1987;OIson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to conclude what compounds identified in any cheese produce its distintictive flavour, and Cheddar is no exception, with different conclusions from various analytical approaches. A flavour component balance theory (Mulder, 1952;McGugan, 1975) is strongly favoured; volatile compounds are almost certainly responsible for flavour character. Non-volatile compounds, found particularly in the aqueous fraction, may be responsible for the cheesiness and the intensity of flavour (Urbach, 1993).…”
Section: What Are the Compounds Responsible For Cheese Flavour?mentioning
confidence: 99%
“…The contributions of volatile sulphur compounds to flavour have received much attention, and many have been identified in cheeses, including H,S, CH,SH, carbonyl sulphide, carbon disulphide, dimethyl sulphide (DMS), dimethyl disu1phi.de (DMDS) (Lindsay & Rippe, 1986), dimethyl trisulphide (McGugan, 1975), methional (Day ef al., 1960 and SO, (Price & Manning, 1983). None has a typical cheese odour, but because of their low odour thresholds a contribution to flavour, for at least some of these, is most likely.…”
Section: What Are the Compounds Responsible For Cheese Flavour?mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and complexity of flavors in various types of cheeses have been subjects of investigation by several researchers ( 10,20,32,63). Although each variety of cheese has its own characteristic flavor, extensive research has shown that all cheese flavors are generated mainly by the interaction of compounds produced by decomposition of milk constituents.…”
Section: Flavor Developmentmentioning
confidence: 99%